The effect of organizational culture, supervision, and punishment on work discipline (Case study on official motorcycle dealers in Madiun City) - Dessyarti, Robby Sandhi; Oktaviana, Putri (Asian Management and Business Review, 2023)
Human resources are an essential factor in the company, without human resources the company's goals will not be achieved. Official motorcycle dealers in Madiun City need superior human resources, tenacious dexterity, and innovation in carrying out the goals of motorcycle dealers to achieve sales targets. An effective way to improve motorcycle sales performance is to improve work discipline. Work discipline is a rule that binds employees to always obey the company. The research objective is to prove whether there is an influence of organizational culture, supervision, and punishment on work discipline. This research was conducted on official motorcycle sales in Madiun City using the non-probability Sampling research method, the technique for determining the population using saturated samples or census with a total of 288 employees. This research method uses a quantitative approach using SmartPLS software. The results of this study show that 1) organizational culture has a positive and significant effect on work discipline. This reflects that the organizational culture at official motorcycle dealers in Madiun City is clear and the rules set have been obeyed by sales so that there is a good working relationship between all motorcycle dealer employees, 2) supervision has a positive and significant effect on work discipline. This shows that supervisors routinely carry out supervision so that it can help the employees of motorcycle dealers, and 3) supervision has a positive and significant effect on work discipline. Implications and future direction are discussed in the last section of this article.